«Samiskheit» i Kunnskapsløftet 2020 : Ei diskursanalytisk lesing av Fagfornyinga - Sem, Leiv Heming; Kolberg, Asbjørn (Nordic Studies in Education, 2022)
What idea of «Saaminess» is presented and produced by the current Saami and non-Saami national curricula of the Norwegian primary school? Our discourse analysis focussing on the interpellation of pupils shows that the two curricula express different attitudes towards Saaminess, and indeed to education. Saami pupils are interpellated primarily into recognizing and strengthening their Saami identity, and less to be critically inclined and independent-minded. In contrast the non-Saami curriculum focus on disciplinary skills, and has critical method as its fundament. Both curricula may be understood as initiations to dogmatic communities of ideology. We conclude that all teachers should read both plans within their fields, as each complement the other. «Samiskheit» i Kunnskapsløftet 2020: Ei diskursanalytisk lesing av Fagfornyinga publishedVersion